Searching the trace of Chuqui Chinchay in Moche territories: Dual subjects in pre-Columbian Peru - Álvarez Chávez, Roland (2020)
Currently, the Character D of the famous Moche Sacrifice Theme constitutes an enigma. Presently there are three possible candidates: the character found in the grave 14, the Lord of Ucupe, and finally although discarded, the Lady of Cao, and precisely because of her female sex. In this sense, this article is mainly an adventure of research ranging from chronicles to gender theory, including iconography, in order to demonstrate from iconographic material and historiographic data, a possible trace that could facilitate the finding of its identity. This trace attempts the possibility of a relationship between the Moche Character D and the divine figure of the Chuqui Chinchay. In this task, I intend to cleverly launch the different clues and evidences that would demonstrate this relationship, which could demonstrate the existence in pre-Hispanic societies of Peru of dual subjects, who apparently had a corporeal treatment that goes between variations of masculine to feminine and vice versa, and framed within ritual practices and ceremonies.